Peluang Wanita Menikah Bekerja di Sektor Informal (Pedagang Kaki lima) di Desa Kemang Indah Kecamatan Tambang Kabupaten Kampar Propinsi Riau - Murialti, Neng (Jurnal Akuntansi dan Ekonomika, 2019)
This study aims to examine the effect of married women's education, husband's occupation, the education of the oldest child, residence status, family dependence and household expenditure on the chances of married women working in the informal sector (street vendors) in Kemang Indah Village, Tambang District, Kampar District . This study uses primary and secondary. The analytical tool used in this study is logistic regression. From the research results obtained from the six independent variables used in this study, three independent variants have a significant effect on the probability of married women to work in the Informal sector namely variables: husband's work, oldest education, residence status, while the other three independent variables are the education variables of married women, Jumah family dependents and household expenditures did not significantly influence the probability of married women in Kemang Indah Village, Tambang District to work in the informa sector (street vendors).